Factors affecting the implementation of occupational safety and health management system (OSHMS) in Malaysia petrochemical industry - Al-Qaisi, Mohammed Murad (2022)
In petrochemical industries, a lot of attention has drawn on this sector due to its high incidence of accidents and fatality rates. Occupational safety and health management system (OSHMS) is essential for accident prevention, and successful implementation of OSHMS heavily depends on several items of contextual factors. Hence, this study was carried out to investigate the effect of 20 items of the independent variable (IV) with five items for each factor of management factor (MF), personal factor (PF), process factor (PRF), and environmental factor (EF) on four items of the dependent variable (DV) of OSHMS implementation in Malaysia petrochemical industry. A questionnaire survey was employed to obtain quantitative data from 150 respondents of the selected petrochemical companies. Then, the quantitative data analyses were performed through descriptive and inferential statistical methods. The validity of the questionnaire was confirmed based on the value of the content validity index (CVI). Besides, the loadings of five sub-factor model for MF, PF, PRF, and EF were statistically significant by conducting confirmatory factor analysis (CFA). Based on mean score results, the descriptive analysis revealed that the sub-factors of facility management (MF5), training (PF2), maintenance (PRF4), and environmental programs (EF5) were considered as the most influencing factors of OSHMS implementation. Meanwhile, the inferential statistical method using correlation and multiple regression analysis (MRA) was adopted to investigate the association between IVs and DV. There was a positive and very strong relationship between all the factors and OSHMS implementation based on the value of the Pearson correlation coefficient obtained. Therefore, this study concluded that these contextual factors should be taken into consideration towards achieving effective implementation of OSHMS, particularly in Malaysia petrochemical industry. Nevertheless, the results of this study are limited to the keywords used for the sub-factors of PF, PRF, and EF, where the sub-factors are explained using the keywords that related to MF activities, which could led to the source of the problem. The results could be more meaningful when the appropriate keywords are used within the sub-factors of MF, PF, PRF and EF.